An Investigation of Auditory and Visual Temporal Processing in Children with Reading Disorders - Smith, Lauren R. (East Carolina University, 2009)
Several lines of research have revealed a relationship between reading disorders (RD) and auditory temporal processing deficits. That is, subtle, yet rapid changes within an acoustic message are more difficult for individuals with RD to perceive than for those individuals with normal reading abilities, which negatively impacts accurate speech perception and, in turn, phonological processing and decoding abilities (Cestnick & Jerger, 2000; De Jong et al, 2000; Fink et al., 2006; Walker et al., 2006). However, researchers investigating a pansensory temporal processing deficit theory of RD have found conflicting evidence supporting the relationship between visual temporal processing and reading, specifically in regards to the magnocellular deficit theory of dyslexia (Chase & Jenner, 1993; Farmer & Klein, 1993; Lehmkuhle et al., 1993; Lovegrove, 1993). The purpose of the current study was to further investigate the relationship between pansensory processing deficits and subtypes of reading disorders. Participants included 27 children (ages 10-13) divided into three reading ability groups (i.e., normal reading, dysphonetic, and dysphoneidetic) based on performance the WRMT-R and Word/Nonword Test. Experimental tasks included gap detection, duration discrimination, and duration temporal order judgment tasks presented in both the auditory and visual modalities. When controlling for verbal ability (PPVT-IV), due to significant group differences, both RD groups (dysphonetic and dysphoneidetic deficits) demonstrated a poorer performance when compared to the control group on both the within- and between-channel gap paradigms of the auditory gap detection task. No significant differences were found between normal, dysphonetic, and dysphoneidetic readers on any of the visual temporal processing tasks. The current study failed to support the pansensory deficit of RD when reading groups were dichotomized across experimental tasks. However, when considering reading abilities as a continuum several significant correlations between performance on auditory and visual experimental tasks and reading decoding standardized measures were found suggesting that pansensory temporal processing is strongly associated with reading abilities. Results suggest that auditory temporal processing abilities are closely linked to phonological decoding skills in addition to sight-word recognition abilities for the young adolescents having reading disorders.
Keywords: Health Sciences, Audiology; Auditory temporal processing; Children; Pansensory temporal processing; Reading disorder subtypes; Reading disorders; Visual temporal processing; Hearing; Dyslexia; Children; Verbal Behavior; Speech Acoustics